Studies on impurity seeding and transport in edge and SOL of tokamak plasma. (18th January 2022) - Raj, Shrish; Bisai, N.; Shankar, Vijay; Sen, A.; Ghosh, Joydeep; Tanna, R.L.; Chowdhuri, Malay B.; Jadeja, K.A.; Assudani, Kumudni; Macwan, Tanmay Martin; Aich, Suman; Singh, Kaushlender
Abstract: We present numerical simulation studies on impurity seeding using nitrogen, neon, and argon gases. These impurity gases are ionized by the electron impact ionization. These ions can be at multiply ionized states, recombine again with the plasma electrons, and radiate energy. The radiation losses are estimated using a non-coronal equilibrium model. A set of 2D model equations to describe their self-consistent evolution are derived using interchange plasma turbulence in the edge and SOL regions and solved using BOUT++. It is found that impurity ions (with single or double-positive charges) move in the inward direction with a velocity ∼0.02 c s so that these fluxes are negative. These fluxes are analyzed for different strengths of an effective gravity that help to understand the impurity ion dynamics. Increased gravity shows an accumulation of certain charged species in the edge region. The radiation loss is seen to have a fluctuation in time with frequency 5–20 kHz that closely follows the behavior of the interchange plasma turbulence. The simulation results on the radiated power and its frequency spectrum compare favourably with observations on the Aditya-U tokamak. The negative fluxes of the impurity ions, their dynamics in the edge region, and the fluctuating nature of the radiation loss are the most important results of this work.